Augmented inhibition of angiogenesis by combination of HER2 antibody chA21 and trastuzumab in human ovarian carcinoma xenograft - Zhang, Anli (BioMed Central, 2010)
BACKGROUND: chA21 is a novel tumor-inhibitory antibody which recognized subdomain I of HER2 extracellular domain with an epitope distinct from other HER2 antibodies. Previously, we demonstrated that chA21 inhibits human ovarian carcinoma cell line SKOV-3 growth in vitro and in vivo study. In this study, we further investigated the anti-angiogenic efficacy combination of chA21 with trastuzumab in SKOV-3 xenograft model. METHODS: Nude mice were s.c. challenged with SKOV-3 cells and received treatment of chA21 alone, trastuzumab alone or both antibodies together twice a week for 21 days. Tumor volume and microvessel density (MVD) were evaluated. The effect of chA21 plus trastuzumab treament on vascular endothelial growth factor (VEGF) secretion, endothelial cells proliferation and migration, and the status of HER2 downstream pathway AKT/phosphorylated AKT (pAKT) were evaluated in vitro. RESULTS: In vivo study combination of chA21 with trastuzumab resulted in reduce tumor growth and angiogenesis than each monotherapy. In vitro study, the combination of chA21 with trastuzumab inhibits VEGF secretion, endothelial cells proliferation and migration. Furthermore, the combination treatment inhibits pAKT expression. CONCLUSION: Our findings suggested that the combination of chA21 with trastuzumab can cause augmented inhibition of angiogenesis in SKOV-3 xenograft model. Inhibition of agniogenesis may through suppression of AKT pathway. The therapeutic benefits of combination chA21 with trastuzumab warrant further study in an attempt to make the translation into the clinic.